Auranofin Attenuates Non-Alcoholic Fatty Liver Disease by Suppressing Lipid Accumulation and NLRP3 Inflammasome-Mediated Hepatic Inflammation In Vivo and In Vitro - Hyun Hwangbo; Min Yeong Kim; Seon Yeong Ji; So Young Kim; Hyesook Lee; Gi-Young Kim; Cheol Park; Young-Sam Keum; Su Hyun Hong; Jaehun Cheong; Yung Hyun Choi (MDPI AG, 2020)
Non-alcoholic fatty liver disease (NAFLD) causes liver dysfunction and is associated with obesity and type 2 diabetes. Chronic inflammation is associated not only with the development of NAFLD, but also with hepatic diseases, including steatohepatitis, cirrhosis, and hepatocellular carcinoma. Auranofin is a treatment for rheumatoid arthritis and has recently been reported to have potential effects against a variety of diseases, including inflammation, cancer, and viral infection. In this study, auranofin may be considered as a new treatment for the management of metabolic syndrome, as well as in the treatment of NAFLD through immunomodulation. To determine the effect of auranofin on NAFLD, C57BL/6 mice were randomly grouped, fed a regular diet or a high fat diet (HFD), and injected with normal saline or auranofin for 8 weeks. Auranofin significantly decreased the body weight, epididymal fat weight, serum aspartate aminotransferase (AST), and glucose, as well as the serum triglyceride, cholesterol, and low-density lipoprotein cholesterol levels as compared to the HFD group. We also observed that hepatic steatosis was increased in the HFD group and was suppressed by auranofin treatment. In addition, auranofin suppressed the expressions of interleukin (IL)-1β, IL-18, caspase-1, and the NOD-like receptor family pyrin domain containing 3 (NLRP3) in the liver tissue. Furthermore, the expression of NADPH oxidase 4 and peroxisome proliferator-activated receptor γ (PPARγ), which are a major source of oxidative stress and a regulator of adipogenesis, respectively, were also decreased by auranofin. In addition, primary mouse hepatocytes were incubated with lipopolysaccharide (LPS) and palmitic acid (PA) to induce lipid accumulation and hepatic inflammation for an in vitro model. Auranofin could significantly inhibit LPS- and PA-induced inflammatory activity including nitric oxide and NLRP3 inflammasome-mediated cytokines. The results of this study demonstrate that auranofin treatment inhibits the characteristics of NAFLD through the inhibition of NLRP3 inflammasome. Therefore, auranofin may have potential as a candidate for improving NAFLD symptoms.